MEMBANGUN PENDIDIKAN KARAKTER SEJAK USIA DINI - Agus Supriyadi (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
Character education is a vital instrument in determining the progress of a nation. Therefore the government needs to build educational institutions in order to produce good human resources that are ready to oversee and deliver the nation at a progressive level. It’s just that in reality, national education is not in line with the ideals of national education because the output is not in tune with moral values on the one hand and the potential for individuals to compete in world intellectual order on the other hand. Therefore, as a solution to these problems is the need for the applicationof character education from an early age.